Using Data Mining Technique to Analyze Student's Performance (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2014)
Educational organizations are one of the important parts of our society and playing a vital role for growth and development of any nation. With the help of Data Mining, which is an emerging technique, one can efficiently learn from historical data and use that obtained knowledge for predicting future behaviour of concern areas. Growth of current education system is surely enhanced if Data Mining has been adopted as a futuristic strategic management tool. The Data Mining tool is able to facilitate better resource utilization in terms of student performance, course development and finally the development of nation's education related standards. This paper focuses on capabilities of data mining in context of education, Also it compare three of the most common data mining techniques (ID3, C4.5 and REPTree).